(untitled) (Engineering Review, 2012)
In the preliminary aerodynamic aircraft design, optimum calculation methods should be used, which enable engineers to perform a vast number of test runs in a reasonably short time. Such tools should not only be fairly simple but also reliable. In the first part, this paper briefly presents aerodynamic analyses performed by a 3D vortex lattice method (VLM), with an aim to verify its capabilities and to give results that coincide well with the experimental data of an existing airplane. Since this computational model is based on inviscid flow concept, effectiveness of control surfaces and flaps are inherently overestimated. In order to compensate for the omitted boundary layer influence, a set of calibration diagrams for effectiveness and circulation influence has been successfully derived and good agreements with wind tunnel test data have been achieved. After several necessary adjustments, calibration functions have been applied to VLM analysis within a new light aircraft conceptual study. Those results have been compared with results obtained by well known Datcom method and verygood agreements have been achieved, proving that VLM computations with properly defined calibration functions can be both efficient and reliable tools in preliminary aerodynamic design.